Sobreprotección Y Relaciones Interpersonales en los Estudiantes de la Unidad Educativa “Camilo Gallegos” Riobamba. Octubre 2017-Marzo 2018”. - Arévalo Barahona, Zoila Inés (2018)
The present investigation took place in the Educational Unit "Camilo Gallegos Toledo" of the city of Riobamba, located in the province of Chimborazo during the period between October 2017-March 2018. In which the students of the seventh year of General Education participated Basic parallels A and B. The purpose of the same was to determine the influence of overprotection in interpersonal relationships, during the period indicated. The present investigation was justified by the predominance of the problem and the need for a correct development of interpersonal relationships to improve coexistence among students and thus promote a proper development of them. The information provided within the research could be obtained through an extensive bibliographical exploration and of course the results obtained through field work. The level of the research is descriptive and non-experimental design. The sample was intentional non-probabilistic established in 56 students of the institution. The Parental Boding Instrument Questionnaire was applied, consisting of 19 questions with the following options: (Always, Sometimes, Never) for the assessment of overprotection, followed by a survey consisting of 10 items with closed questions of (Yes and No) to appreciate the type of interpersonal relationships that the students have developed during their childhood. In this way, it is concluded that overprotection has a great impact on the development of interpersonal relationships in students of educational institutions.